Failure of the market, state and economics from the perspective of the financial crisis - Godłów-Legiędź, Janina (Comparative Economic Research. Central and Eastern Europe, 2011)
The debate between the advocates of market and interventionist solutions, primarily based on pitting the market against regulation, has escalated as a result of the financial crisis. The objective of the paper is not only to analyze the advantages and drawbacks of alternative regulatory mechanisms in the light of the global economic downturn, but also to evaluate the modern economy from this perspective. The paper focuses on three hypotheses. 1. It is illegitimate to pit the market against regulation. 2. The crisis resulted from the violation of the principles of classical liberalism, which was precipitated both by inadequate policies and by modern economic methodology. 3. Critical analysis of the methodology and logic of the development of 20th century economic thought reveals the existence of a systemic failure of the dominant doctrines in mainstream economics.